Cardiovascular disease prevention in the worksite: Where are we?. (1st December 2022) - Biffi, Alessandro; Fernando, Fredrick; Palermi, Stefano; Sirico, Felice; Bonatesta, Lorenzo; Cavarretta, Elena; D'Ascenzi, Flavio; Niebauer, Josef
Abstract: The current guidelines of the European Society of Cardiology on cardiovascular (CV) disease prevention highlighted the importance of implementing coordinated set of action, including worksite, aimed at eliminating or minimizing the impact of CV disease and their related disabilities. Workplace wellness programs tend to focus on modifiable risk factors of non-communicable disease, such as nutrition, physical activity, and smoking cessation. However, nowadays, corporate wellness programs are still rare and incomplete, and usually received limited attention. This represents a big public health issue since company health and wellness interventions may provide an important opportunity to identify and manage CV risk. Given the increasing of employees' average age, a progressive shifting of retirement age and an increased number of chronic diseases, these preventive programs will increasingly represent key factors of both employee's health and economic strategies of companies in the near future. Highlights: Programs aimed at prevention of cardiovascular disease in the working population are still rare and incomplete Published evaluations yielded mixed results If properly organized and conducted, corporate wellness program can represent a key strategy for cardiovascular prevention